Divisible quantum dynamics satisfies temporal Tsirelson's bound. (4th January 2017) - Le, Thao; Pollock, Felix A; Paterek, Tomasz; Paternostro, Mauro; Modi, Kavan
Abstract: We give strong evidence that divisibility of qubit quantum processes implies temporal Tsirelson's bound. We also give strong evidence that the classical bound of the temporal Bell's inequality holds for dynamics that can be described by entanglement-breaking channels—a more general class of dynamics than that allowed by classical physics.